Kit ligand has a critical role in mouse yolk sac and aorta–gonad–mesonephros hematopoiesis. (30th August 2018) - Azzoni, Emanuele; Frontera, Vincent; McGrath, Kathleen E; Harman, Joe; Carrelha, Joana; Nerlov, Claus; Palis, James; Jacobsen, Sten Eirik W; de Bruijn, Marella FTR
Abstract: Few studies report on the in vivo requirement for hematopoietic niche factors in the mammalian embryo. Here, we comprehensively analyze the requirement for Kit ligand (Kitl) in the yolk sac and aorta–gonad–mesonephros (AGM) niche. In‐depth analysis of loss‐of‐function and transgenic reporter mouse models show that Kitl‐deficient embryos harbor decreased numbers of yolk sac erythro‐myeloid progenitor (EMP) cells, resulting from a proliferation defect following their initial emergence. This EMP defect causes a dramatic decrease in fetal liver erythroid cells prior to the onset of hematopoietic stem cell (HSC)‐derived erythropoiesis, and a reduction in tissue‐resident macrophages. Pre‐HSCs in the AGM require Kitl for survival and maturation, but not proliferation. Although Kitl is expressed widely in all embryonic hematopoietic niches, conditional deletion in endothelial cells recapitulates germline loss‐of‐function phenotypes in AGM and yolk sac, with phenotypic HSCs but not EMPs remaining dependent on endothelial Kitl upon migration to the fetal liver. In conclusion, our data establish Kitl as a critical regulator in the in vivo AGM and yolk sac endothelial niche. Synopsis: Genetic mouse models reveal a critical requirement for Kitl in yolk sac and dorsal aorta hematopoietic niches. HSCs, but not erythro‐myeloid progenitors, remain dependent on endothelial Kitl upon migration to the fetal liver. Kit ligand is required for the expansion of erythro‐myeloid progenitors in the yolk sac and fetal liver. HSCs depend on endothelial Kitl throughout their development. Yolk sac erythro‐myeloid progenitors no longer require endothelial Kitl upon migration to the fetal liver. Abstract : Genetic mouse models reveal a critical requirement for Kitl in yolk sac and dorsal aorta hematopoietic niches. HSCs, but not erythro‐myeloid progenitors, remain dependent on endothelial Kitl upon migration to the fetal liver.